Sexual Abuse Characteristics and Psychological Functioning among Male Survivors of Childhood Sexual Abuse - Lyons, Jennifer (Université d'Ottawa / University of Ottawa, 2018)
Childhood sexual abuse among males has been associated with many negative psychological outcomes. Studies have attempted to identify which sexual abuse characteristics (e.g., duration, age of onset) are associated with mental health difficulties. While informative, this research has been mostly limited to variable-centered analyses, which do not capture the heterogeneity in males’ abuse experiences and psychological presentations. This two-part dissertation advances our understanding of how best to measure childhood sexual abuse and how to account for the diversity of sexual abuse experiences and outcomes among men using a person-centered approach. Given that there are few validated measures of childhood sexual abuse, the first study examined the psychometric properties of a commonly-used measure in the sexual abuse literature, the Sexual Victimization Survey (SVS; Finkelhor, 1979). Once the validity and reliability of the SVS were established, the SVS was used to generate profiles on the basis of abuse characteristics (Study 2). Data for both studies were drawn from a sample of 302 males (85% Caucasian) aged 18 to 65 years seeking support for childhood sexual abuse. Participants completed a modified version of the SVS as well as the sexual abuse subscale of the Childhood Experiences of Violence Questionnaire-Short Form (CEVQ-SF; Tanaka et al., 2012). Twenty-one males completed the SVS again one week later for test-retest purposes. The SVS showed high inter-rater reliability on sexual abuse status and sexual abuse characteristics. Most males (85%) who endorsed sexual abuse on the SVS did so on the CEVQ-SF, resulting in fair concurrent validity. The SVS showed perfect one-week test-retest reliability on abuse status, as well as good to excellent agreement on sexual abuse characteristics between the initial and one week time points. Given the strong psychometric properties of the modified SVS, it was then used to generate childhood sexual abuse profiles in Study 2. Once participants with significant missing data were deleted, 215 men remained and were included in the generation of profiles. Latent profile analyses revealed three distinct profiles which varied in the severity of abuse experiences. The Severe profile (n = 56, 26%) depicted sexual abuse which began in mid-childhood and consisted of a one or two time fondling by an unfamiliar extrafamilial perpetrator. Men in the More Severe profile (n = 71, 33%) also experienced abuse in mid-childhood by an extrafamilial perpetrator, but experienced more severe sexual acts that spanned several months to several years. Men in this profile were emotionally closer to their perpetrators prior to abuse onset than males in the Severe profile. The Most Severe profile (n = 88, 41%) depicted abuse which began in early childhood and consisted of very severe sexual acts by trusted individuals both within and outside of the family. Men in the Most Severe were significantly more likely to concurrently have experienced child emotional and physical abuse as well as a greater number of non-victimization adversities, compared with men in the other two profiles. Profiles varied with respect to psychological outcomes. Males in the More Severe and Most Severe profiles reported significantly more internalizing problems than men in the Severe profile, and men in the Most Severe profile reported significantly more trauma symptoms than men in the Severe profile. Certain contextual variables were also associated with greater psychological difficulties, namely greater present-day use of avoidant coping predicted more internalizing and externalizing problems, as well as greater trauma symptoms. Worse childhood family functioning was associated with more internalizing and externalizing problems, and disclosure of the abuse (compared to non-disclosure) was associated with more externalizing problems and trauma symptoms. These results have several research and clinical implications, including tailoring assessment and treatment to meet the individual needs of male survivors.
Keywords: child sexual abuse; child maltreatment; person-centered; profiles